Status of thyroid hormones in blood plasma of goats at different ages and their correlation with other biochemical parameters* - BHOOSHAN, NEERU; KUMAR, PUNEET; SINGH, S K; YADAV, M C (The Indian Journal of Animal Sciences, 2010)
Healthy female goats (156: 78 Barbari and 78 Jamunapari goats) of different age groups, managed under semiintensive system of production in semiarid and tropical region were utilized. Blood was collected at days 0 (birth), 30, 90, 180, 270–300, 330–360 besides pre-pubertal, pubertal and post-pubertal (1 week after estrus) ages. Plasma concentration of thyroxine (T4) and 3–3’-5-triiodothyronine (T3) were significantly influenced by the breed and age of the goats. Significantly highest concentration of T4 hormone in both the breeds was recorded at birth. After birth, T4 level decreased sharply and attained significant lower values at 1 month of age in Barbari goats. In Jamunapari goats, T4 concentration was lower at 30 and 90 days of age compared to all other stages. T4 concentration started increasing after 1 month of age in Barbari goats and after 3 months of age in Jamunapari goats and remained at significantly high level up to 330–360 days of age. In Jamunapari goats, the highest level was also seen at the age of 270–300 days. At prepubertal, pubertal and post pubertal age, T4 concentration did not fluctuate significantly. In Barbari goats, T3 concentration did not change since birth to post-pubertal age except a decrease at 90 days age. In Jamunapari goats, T3 concentration was generally stable except an increase at 180 days and pubertal age. The plasma T4 and T3 hormones were positively correlated with estrogen. T4 had positive correlation with progesterone. T3 hormone had significantly positive correlation with mean corpuscular haemoglobin concentration, serum glutamate oxaloacetate transaminase, serum glutamate pyruvate transaminase, amylase, total proteins, total globulin, cholesterol and estrogen.